[Mechanical sugar cane harvester in operation] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Mechanical self-loading tractor which harvests and loads the cane in the fields.
Cataloger's title